Relationship between Behavior and Work Accident in Rice Farmers using Pesticides in Oebobo Village, Batu Putih District - Bryan, Joss; Ratu, Jacob; Oematan, Grouse; Umbu Roga, Anderias (Asian Journal of Logistics Management, 2022)
Work accident cases are a health problem in many parts of the world, including in the East Nusa Tenggara region. This study aims to analyze the relationship between behavior and work accidents among rice farmers who use pesticides in Oebobo village, Batu Putih district. This type of research uses an analytic survey with a cross-sectional design. The study's results were analyzed statistically using the chi-square test showing the relationship between knowledge and work accidents obtained a score (p-value) of 0.023, and the relationship between attitudes and work accidents got a score (p-value) of 0.044. The relationship between action and work accidents, a score (p-value) of 0.030 was obtained so that statistically, there was a relationship between behavior and work accidents on pesticide-using rice in Oebobo Village, Batu Putih District. This research contributes to knowing the causes of work accidents among farmers who use pesticides, namely lack of knowledge, attitudes that do not want to use personal protective equipment, and unsafe actions at work. The use of PPE by rice farmers is still deficient. The majority of farmers generally still feel indifferent about this. The findings obtained in this study indicate that knowledge, attitudes, and actions are related to work accidents among rice farmers who use pesticides in Oebobo Village, Batu Putih District. In the future, there needs to be more intense outreach by either village assistants or other related parties in order to increase the knowledge and understanding of the farmers in the village, as well as prevent work accidents in the future.